Cytokine Storm Syndrome Responsive to IL-1 Inhibition in Trisomy 21 - Aimee Magnarelli; Julia Shalen; Maria J. Gutierrez (Case Reports in Pediatrics)
Background. Cytokine storm syndromes (CSS) are life-threatening systemic inflammatory disorders caused by immune system dysregulation. They can lead to organ failure and are triggered by various factors, including infections, malignancy, inborn errors of immunity, and autoimmune conditions. Trisomy 21 (TS21), also known as Down syndrome, is a genetic disorder associated with immune dysfunction, increased infection susceptibility, and inflammation. While TS21 has been linked to infectious-triggered hyperinflammation, its role as a primary cause of CSS has not been confirmed. Case Presentation. We present a case of a 16-year-old male with TS21 with fever, rash, joint pain, and abdominal symptoms. Extensive investigations ruled out infections, autoimmune conditions, malignancies, and inborn errors of immunity as triggers for a CSS. The patient’s symptoms improved with treatment using IL-1 inhibition and corticosteroids. Conclusions. This case reinforces that TS21 is an immune dysregulation disorder and highlights the importance of considering CSS in TS21 patients, even when triggers are unclear. The positive response to IL-1 inhibition in this patient suggests that dysregulation of the IL-1 superfamily and the NLRP3 inflammasome may contribute to CSS in TS21. This finding raises the possibility of using IL-1 inhibition as a treatment approach for CSS in TS21 patients.